دراسة الخواص الفيزوميكانيكية والكيميائية لخلائط المطّاط الطبيعي والأسمنت الحراري - علي, علي; شاش, ميساء; مخلوف, أحمد (Latakia University Journal -Engineering Sciences Series, 2017)
تم في هذا البحث دراسة تأثير إضافة الأسمنت الحراري كمادة مالئة على خواص المطّاط الطبيعي STR20، عن طريق تحضير خلائط من المطّاط الطبيعي تحتوي نسب مختلفة من الأسمنت الحراري (20,15,10,5,0 pphr) على جهاز درفلة المطّاط ثم توصيف الخواص الفيزوميكانيكية والكيميائية للخلائط المحضرة, وذلك باختبارها لقياس مقاومة الشد، ومقاومة الاحتكاك وتحديد كل من قيم القساوة والإنتباجية في مذيبات مختلفة. أظهرت النتائج ازدياد مقاومة الشد مع زيادة نسبة الأسمنت الحراري حتى (15 pphr) لكن بعد هذه النسبة تأخذ مقاومة الشد بالانخفاض التدريجي, حيث تصبح العلاقة عكسية بين نسبة الإضافة والمقاومة, كما لوحظ انخفاض نسبة الاستطالة عند القطع تدريجيا مع زيادة نسبة إضافة الأسمنت الحراري, أما بالنسبة لقيم القساوة فقد ازدادت بشكل طردي مع زيادة نسبة الأسمنت الحراري في الخلائط، أيضا لوحظ انخفاض في مقاومة الاحتكاك مع زيادة نسبة الإضافة حتى (15 pphr) لترتفع بعد ذلك. كما أظهرت نتائج الدراسة بأن إنتباجية العينات في الزيت المعدني كانت اخفض مقارنة بكل من البنزين والمازوت, ففي الزيت المعدني كانت الإنتباجية بنسبة %1.29, أما في البنزين كانت بنسبة %14.15 وفي المازوت بنسبة %12.43. In this research study the effect of adding thermal cement as a filler on the properties of natural rubber STR20, through the preparation of natural rubber mixtures containing different ratios of thermal cement (0,5,10,15,20 pphr) on the rolling rubber machine, then characterization physico-mechanical properties and chemical of mixtures that prepared and then tested to measure the tensile strength, resistance friction and determine the hardness and swelling values in different solvents.The results showed increased tensile strength with increased thermal cement ratio until (15 pphr) but after this percentage take tensile strength to decline gradually, where the relationship becomes counterproductive between the additives and the resistance ratio, as noted the low percentage of elongation at break gradually with increasing the proportion of thermal cement, as for the hardness values it has increased in extrusive with increase the proportion of thermal cement in mixtures, also observed a decrease in friction resistance with increase the additives proportion even (15 pphr) to rise after that.Results of the study also showed that the samples swelling in mineral oil was lower compared to all of the gasoline and diesel, the swelling was in the mineral oil 1.29%, while in gasoline was 14.15% and in diesel was 12.43%.